2007
DOI: 10.1111/j.1365-3156.2007.01855.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting home delivery in rural Tanzania

Abstract: Summarybackground Studies of factors affecting place of delivery have rarely considered the influence of gender roles and relations within the household. This study combines an understanding of gender issues relating to health and help-seeking behaviour with epidemiological knowledge concerning place of delivery.methods In-depth interviews, focus group discussions and participant observation were used to explore determinants of home delivery in southern Tanzania. Quantitative data were collected in a crosssect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
288
5
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(350 citation statements)
references
References 26 publications
55
288
5
2
Order By: Relevance
“…Delivery at health facilities needs to be more easily accessible (Campbell and Graham, 2006;Koblinsky, 2006;Ronsmans and Graham, 2006), although it should be noted that there is a major shortage of skilled birth attendants at peripheral health facilities in our study area. Our observations suggest that even mothers who are aware of the health risks in childbirth have problems accessing good care at health facilities due to lack of money, poor transport, abusive language and drug shortages (Mrisho et al, 2007). Moreover, health staff give more emphasis to advising primigravidae to give birth in a facility than to multigravid mothers.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Delivery at health facilities needs to be more easily accessible (Campbell and Graham, 2006;Koblinsky, 2006;Ronsmans and Graham, 2006), although it should be noted that there is a major shortage of skilled birth attendants at peripheral health facilities in our study area. Our observations suggest that even mothers who are aware of the health risks in childbirth have problems accessing good care at health facilities due to lack of money, poor transport, abusive language and drug shortages (Mrisho et al, 2007). Moreover, health staff give more emphasis to advising primigravidae to give birth in a facility than to multigravid mothers.…”
Section: Discussionmentioning
confidence: 85%
“…More than half (58%) of births are at home (Mrisho et al, 2007). Trained and untrained TBAs assist 16% and 40% of births in Lindi and Mtwara, respectively.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…First, as in other published work 7,12 , SBA has been approximated to health facility delivery, yet some facilities lack staff who can provide SBA 2 . Asking women about their attendant could have addressed this, but there is evidence of inaccurate identification of attendants' skill level by women 25 .…”
Section: =464mentioning
confidence: 94%
“…ANC is in turn a determinant of SBA. In Tanzania, studies in areas of intermediate coverage have found SBA to be significantly associated with distance to facility in two studies, and with socio-economic status (SES) in one study, but not in others 6,[11][12][13] . No published studies have addressed quantitative determinants of ANC in Tanzania.…”
Section: Introductionmentioning
confidence: 99%